Reduce liability in potential COVID‐19‐transmission cases - O'Brien, Timothy (College Athletics and the Law, 2020)
The pandemic will likely trigger a wave of claims and litigation. Lawsuits are already being filed in response to institutional and conference decisions not to play sports in the fall and the cancellations of sponsorship arrangements. Disputes over transmission of COVID‐19 during practice and competition are likely right around the corner. Unlike a workers’ compensation system established as the exclusive remedy to compensate employees for work‐related illnesses and injuries, college athletics doesn't offer a compensation system for student‐athletes who contract the virus.